The effect of mining and road development on habitat fragmentation and connectivity of khulan (Equus hemionus) in Northwestern China - Zhuo, Yingying; Xu, Wenxuan; Wang, Muyang; Chen, Chen; da Silva, António Alves; Yang, Weikang; Ruckstuhl, Kathreen E.; Alves, Joana (Biological conservation, 2022)
Habitat use by wild animals may be subject to spatial and temporal changes. The Kalamaili Mountain Ungulate Nature Reserve (KNR), inhabited by >80 % of Chinese khulan (Equus hemionus), is one of the most important desert ungulate reserves in Northwestern China. However, frequent human disturbance caused by mining development and road construction in KNR has interfered with or completely blocked their movement and access to parts of the reserve. In our study, we assessed the distribution of suitable habitat and ecological corridors of khulan before the mining development (2005), at the peak of mining development (2011), and after ecological restoration and expressway construction (2019). The results showed that most of the core habitat and ecological corridors of khulan were concentrated in the middle of the reserve and on the east side of the road. The habitat of khulan in KNR went from a good natural habitat in 2005 to deterioration due to mining development in 2011. Then it partially recovered due to ecological restoration from 2015 onwards. However, in 2019, road construction likely hindered its recovery to pre-mining levels. The location of corridors accordingly varied with the change of core habitat in different years. Nevertheless, the corridors intersecting roads generally had higher centrality values, indicating their higher importance. Our study revealed the significant impacts that mining development and road construction have had on the distribution of core habitats, ecological corridors, and movement of khulan. These results provide a scientific basis and valuable arguments for strengthening habitat connectivity for khulan.